The “Structural Interplay”: Deviated Septal Angle and Pneumatization of Bulla - A Retrospective Study - Asmitha, Asmitha; M, Ujval.; A, Sagayaraj.; Mohiyuddin, Azeem (Journal of Neonatal Surgery, 2025)
Introduction: Concha bullosa (CB) refers to the pneumatization of the concha, typically the middle turbinate. The precise mechanism of the CB remains ambiguous; nonetheless, the airflow pattern within the nasal cavity is deemed to be significant. The reduced airflow in the nasal cavity, due to the convexity of the deviation, results in increased pneumatization. While clinical practice findings typically support this, there is insufficient quantitative research validating the association between the angle of deviation and the degree of pneumatization. Objective: 1. To estimate the association of concha bullosa in cases with septal deviation; To find the relationship between the angle of deviation and degree of pneumatization. Methods: This is a retrospective study conducted in R.L. Jalappa Hospital conducted between Jan 2023-Nov 2024. Around 157 CT scans were studied by convenience sampling. Then nasal septal angle and Pneumatisation index was recorded. The data collected were analysed using Epi info 7. Results: Among 157 paranasal CT scans analysed, the majority were males aged 20–40 years. Isolated septal deviation (29.9%) was the most common finding, followed by combined concha bullosa with septal deviation (24.8%). Laterality differences were significant, with unilateral CB predominating in CB + SD cases (P = 0.046). Mean septal deviation angles significantly differed across groups (P = 0.0001), while CBPI values showed no significant variation between subgroups. Conclusion: Our study concludes that bilateral concha bullosa is common in isolated CB cases and unilateral CB is most common in CB with S.D cases. Also mean septal deviation is higher in unilateral septal deviation with CB compared to bilateral one.